The proteasome controls presynaptic differentiation through modulation of an on-site pool of polyubiquitinated conjugates - Pinto, Maria J. (2017)
Differentiation of the presynaptic terminal is a complex and rapid event that normally occurs in spatially specific axonal regions distant from the soma; thus, it is believed to be dependent on intra-axonal mechanisms. However, the full nature of the local events governing presynaptic assembly remains unknown. Herein, we investigated the involvement of the ubiquitin-proteasome system (UPS), the major degradative pathway, in the local modulation of presynaptic differentiation. We found that proteasome inhibition has a synaptogenic effect on isolated axons. In addition, formation of a stable cluster of synaptic vesicles onto a postsynaptic partner occurs in parallel to an on-site decrease in proteasome degradation. Accumulation of ubiquitinated proteins at nascent sites is a local trigger for presynaptic clustering. Finally, proteasome-related ubiquitin chains (K11 and K48) function as signals for the assembly of presynaptic terminals. Collectively, we propose a new axon-intrinsic mechanism for presynaptic assembly through local UPS inhibition. Subsequent on-site accumulation of proteins in their polyubiquitinated state triggers formation of presynapses.